2017
DOI: 10.3390/nano7050098
|View full text |Cite
|
Sign up to set email alerts
|

Calcination Method Synthesis of SnO2/g-C3N4 Composites for a High-Performance Ethanol Gas Sensing Application

Abstract: The SnO2/g-C3N4 composites were synthesized via a facile calcination method by using SnCl4·5H2O and urea as the precursor. The structure and morphology of the as-synthesized composites were characterized by the techniques of X-ray diffraction (XRD), the field-emission scanning electron microscopy and transmission electron microscopy (SEM and TEM), energy dispersive spectrometry (EDS), thermal gravity and differential thermal analysis (TG-DTA), and N2-sorption. The analysis results indicated that the as-synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Figure 2e displays the typical TEM image of the Co 3 O 4 /pCNH composite. The morphology and microstructure of pCNH has been verified with thin layers in our previous paper [25]. It can be seen from Figure 2e that polymeric to graphitic carbon nitride (pCNH) support the Co 3 O 4 particles, and the Co 3 O 4 nanoparticles are highly dispersed on the surface of pCNH nanosheet, and the high surface area of pCNH nanosheet can suppress the sintering of Co 3 O 4 nanoparticles.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 2e displays the typical TEM image of the Co 3 O 4 /pCNH composite. The morphology and microstructure of pCNH has been verified with thin layers in our previous paper [25]. It can be seen from Figure 2e that polymeric to graphitic carbon nitride (pCNH) support the Co 3 O 4 particles, and the Co 3 O 4 nanoparticles are highly dispersed on the surface of pCNH nanosheet, and the high surface area of pCNH nanosheet can suppress the sintering of Co 3 O 4 nanoparticles.…”
Section: Resultssupporting
confidence: 58%
“…Chen et al reported that Co 3 O 4 -rGO nanoparticles showed a good response and recovery to methanol [24]. Cao et al synthesized the SnO 2 /g-C 3 N 4 composites with high performance to ethanol via a facile calcination method [25]. Actually, reports on Co 3 O 4 as gas sensor are limited, and there is no report on Co 3 O 4 decorated pCNH composite for gas sensor application.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent properties and novel applications in gas sensors, people have made great efforts to develop different nanostructured materials to improve the performances [6,7,8]. Especially, various novel nanostructures based on SnO 2 semiconducting oxides, such as nano films [9], hollow nanofibers [10], nanocomposites [11,12], porous architecture [13], and so on, have been extensively investigated as a promising candidate for gas sensing materials.…”
Section: Introductionmentioning
confidence: 99%
“…Graphitic carbon nitride (g-C 3 N 4 ) was synthesized by our previous reported method [30,31]. MgFe 2 O 4 /g-C 3 N 4 composites were prepared by a facile solvothermal process.…”
Section: Methodsmentioning
confidence: 99%